TÓLEPBERGEN QAYÍPBERGENOVTÍŃ “BAXÍTSÍZLAR” ROMANÍNDA NAQÍL-MAQALLARDÍŃ QOLLANÍLÍW ÓZGESHELIKLERI - Kırkbaev, Arıslanbay Sultanbay ulı (Educational Research in Universal Sciences, 2023)
This article is about the usage of proverbs in the novel of “Baxitsizlar” (“The depondents”) by Tulepbergen Kayipbergenov. In this article it was give some explanations about the variable proverbs which were used in the novel. It contains examples of proverbs of rearranged construction of their components.